2019
DOI: 10.3390/ijms20215425
|View full text |Cite
|
Sign up to set email alerts
|

Cytoprotective Effect of Antioxidant Pentapeptides from the Protein Hydrolysate of Swim Bladders of Miiuy Croaker (Miichthys miiuy) against H2O2-Mediated Human Umbilical Vein Endothelial Cell (HUVEC) Injury

Abstract: In our previous research, ten antioxidant pentapeptides including FYKWP, FTGMD, GFEPY, YLPYA, FPPYERRQ, GFYAA, FSGLR, FPYLRH, VPDDD, and GIEWA were identified from the hydrolysate of miiuy croaker (Miichthys miiuy) swim bladder. In this work, their protective function on H2O2-induced oxidative damage to human umbilical vein endothelial cells (HUVECs) was studied. Results indicated that there was no significant difference in the HUVEC viability between the normal group and the treated groups with the 10 pentape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(64 citation statements)
references
References 44 publications
0
64
0
Order By: Relevance
“…ROS are generated by different physiological and biochemical oxidative processes in the organisms and associated with numerous physiological and pathophysiological processes [41,42]. At high levels, ROS damage some key biological macromolecules and play a major role in the pathogenesis of various human diseases [43,44]. The present data indicated that MMP-4, MMP-7, and MMP-12 could protect cells from the damage of ROS.…”
Section: Protection Of Mmp-4 Mmp-7 and Mmp-12 On H 2 O 2 -Induced Omentioning
confidence: 55%
“…ROS are generated by different physiological and biochemical oxidative processes in the organisms and associated with numerous physiological and pathophysiological processes [41,42]. At high levels, ROS damage some key biological macromolecules and play a major role in the pathogenesis of various human diseases [43,44]. The present data indicated that MMP-4, MMP-7, and MMP-12 could protect cells from the damage of ROS.…”
Section: Protection Of Mmp-4 Mmp-7 and Mmp-12 On H 2 O 2 -Induced Omentioning
confidence: 55%
“…Furthermore, the MDA level in the high-dose group was similar to the MDA amount in the control group. In addition, Cai et al [ 36 ] reported that FPYLRH (S8) from the swim bladders of Miiuy Croaker ( Miichthys miiuy ) can up-regulate the levels of SOD and GSH-Px, and down-regulate the contents of MDA, suggesting that it plays a protective role in the antioxidant effects on HUVECs against H 2 O 2 -induced injury.…”
Section: Resultsmentioning
confidence: 99%
“…Some BAPs that protect HUVECs from oxidative stress has been reported, and most are hydrolysates. Two peptides with the sequence of Lys-His-Asn-Arg-Gly-Asp-Glu-Phe from rice bran protein and Phe-Pro-Tyr-Leu-Arg-His from miiuy croaker protein showed the cytoprotective effect with the increased cell viability in H 2 O 2 -induced HUVECs injury [40,41]. Comparing the sequence of two BAPs and those in the literature, there are antioxidant amino acids such as Tyr, His, Pro, Phe, Trp, and Lys (N-terminal), but there is no similarity in the sequence.…”
Section: Discussionmentioning
confidence: 98%